Vaccination completeness in children with rheumatic diseases: A longitudinal, observational multicenter cohort study in Switzerland - Welzel, Tatjana; Kuemmerle-Deschner, Jasmin; Sluka, Constantin; Carlomagno, Raffaella; Cannizzaro Schneider, Elvira; Kaiser, Daniela; Hofer, Michael; Hentgen, Veronique; Woerner, Andreas (Frontiers in Pediatrics, 2022)
Introduction: Children with rheumatic diseases (PRD) have an increased infection risk. Vaccinations are effective to avoid vaccine-preventable diseases. This study aimed to assess the vaccination completeness in Swiss PRD patients stratified by immunosuppressive treatment (IST). Material and Methods: This multicenter observational cohort study of PRD patients was performed in Basel, Geneva, Lucerne, Lausanne, and Zurich in PRD patients aged <18 years included in the Juvenile Inflammatory Rheumatism Cohort. Completeness was assessed for i) the overall vaccination status (Swiss national immunization program (NIP) and specific additional PRD-recommended vaccinations), ii) for all and each vaccination of the NIP at PRD diagnosis and reference date (RefD) and iii) all and each specific additional PRD-recommended vaccination at RefD. Completeness was assessed over the disease course and stratified by IST. Results: Of 616 eligible patients, 234 children were analyzed. Of these, 147 (63%) were girls. Median age at PRD diagnosis was 6.5 years (IQR 2.9-10.3) and 10.9 years at RefD (6.9-14.3). The median follow-up since PRD diagnosis was 3 years (1.1-5.5). 120/234 children received IST. At RefD, overall vaccination completeness was 3.8% (9/234 children), completeness for the NIP vaccinations was 70.1% (164/234 children; IST 65%, no IST: 75.8%) and for all specific additional PRD-recommended vaccinations was 3.8% (9/234 children; IST 2.5%; no IST 5.3%). Vaccination completeness against pneumococcal disease, hepatitis B virus, and human papilloma virus was 50.4%, 20%, 37.9% respectively. In 25/35 children with negative varicella zoster virus history vaccination status was complete (IST: 94.4%, no IST: 47%). Annual non-live influenza vaccination was complete in 24.4% of children during IST; adherence decreased over the disease course. Discussion: This study identified a low overall vaccination completeness in children with PRD. Particularly, the completeness of specific additional PRD-recommended vaccinations was low. If not performed early after PRD diagnosis, vaccination status remained frequently incomplete. Close collaboration between pediatrician and rheumatologist to improve vaccination completeness is essential. Exchange of vaccination records, standardized assessment of specific PRD-recommended vaccinations and those of the NIP, and annual reminder for influenza vaccination are crucial to improve vaccination completeness in this vulnerable pediatric population.